Pengaruh Liang Boleophthalmus pectinirostris (Linnaeus, 1758) (Actinopterygii:Gobiidae) terhadap Biomassa Mikrofitobenthos di Ekosistem Mangrove Pandansari Brebes Jawa Tengah - Allsay K.A. Cintra; Selvia Oktaviyani; Tyani Fitrian; Nurul D.M. Sjafrie (Jurnal Kelautan Tropis, 2020)
Mudskippers (Boleophthalmus pectinirostris) in temperate climates make burrows and shallow ponds surrounded by mud walls as a provider of microhabitats for microphytobenthos. In the mangrove ecosystem of Pandansari Brebes there are also Boleophthalmus pectinirostris which make burrows. The purpose of this study is to determine the effect of the Boleophthalmus pectinirostris burrow as a microhabitat for microphytobenthos in the mangrove ecosystem of Pandansari, Kaliwlingi village, Brebes. This research was conducted in mangrove and mudflat beach areas with three transects and three replications each. Samples were taken were burrow structures, temperature, and microphytobenthos biomass in the inner and outer area of the burrow. The results showed a total area of burrows in mudflat beach areas 71.93 ± 24.9cm2/m2 was greater than in mangrove areas 50.51 ± 46.9cm2/m2 because the beach has more mud than in mangrove. Microphytobenthos biomass was fewer in mudflat beach areas than mangrove areas because the density of Boleophthalmus pectinirostris was more on the mudflat. There was no difference in microphytobenthos biomass inside the burrow (mangrove: 1623 ± 1108µg/mm2; mudflat beach: 94.5 ± 67.5µg/mm2) from outside the burrow (mangrove: 2484 ± 3161µg/mm2; mudflat beach: 145 ± 151µg/mm2). This shows that the Boleophthalmus pectinirostris burrow in Pandansari Brebes does not provide microhabitats for microphytobenthos. This is because in the tropics the temperature is almost the same every year so that microphytobenthos can always live every year.  Ikan gelodok (Boleophthalmus pectinirostris) di daerah beriklim temperate membuat liang dan juga kolam dangkal yang di kelilingi oleh dinding lumpur sebagai penyedia mikrohabitat bagi mikrofitobenthos. Di ekosistem mangrove Pandansari Brebes juga terdapat B. pectinirostris yang membuat liang. Tujuan penelitian ini mengetahui pengaruh liang ikan gelodok jenis B. pectinirostris sebagai mikrohabitat bagi mikrofitobenthos di ekosistem mangrove daerah Pandansari desa Kaliwlingi Brebes. Penelitian ini dilakukan di daerah mangrove dan daerah pantai berlumpur dengan masing tiga transek dan tiga ulangan. Sampel yang diambil berupa struktur liang, suhu dan biomassa mikrofitobenthos di area dalam dan luar liang. Hasil menunjukan luas liang total lebih besar di daerah pantai 71,93±24,9 cm2/m2 karena pantai memiliki lumpur yang banyak daripada di daerah mangrove 50,51±46,9cm2/m2. Biomassa mikrofitobenthos lebih sedikit di daerah pantai daripada daerah mangrove karena kepadatan B. pectinirostris lebih banyak di pantai. Tidak ada perbedaan biomassa mikrofitobenthos secara signifikan di dalam liang (mangrove: 1623±1108µg/mm2; pantai: 94,5±67,5µg/mm2) dengan di luar liang (mangrove: 2484±3161µg/mm2; pantai:145±151µg/mm2) hal ini menunjukan liang B. pectinirostris di Pandansari Brebes tidak menyediakan mikrohabitat bagi mikrofitobenthos. Hal ini disebabkan di daerah tropis suhu tiap tahun yang hampir sama sehingga mikrofitobenthos dapat selalu hidup tiap tahun